Tracheobronchitis in children with tracheostomy tubes: Overview of a challenging problem. Issue 4 (11th January 2022) - Gipsman, Alexander; Prero, Moshe; Toltzis, Philip; Craven, Daniel
Abstract: Tracheobronchitis is common in children with tracheostomy tubes. These children are predisposed to respiratory infections due to the bypassing of normal upper airway defense mechanisms by the tracheostomy, bacterial colonization of the tracheostomy tube itself, and underlying medical conditions. Diagnosis of bacterial tracheobronchitis is challenging due to the difficulty in differentiating between bacterial colonization and infection, as well as between viral and bacterial etiologies. Difficulty in diagnosis complicates management decisions, and there are currently no consensus guidelines to assist clinicians in the treatment of these patients. Frequent administration of systemic antibiotics causes adverse effects and leads to the emergence of resistant organisms. Topical administration of antibiotics via nebulization or direct instillation may lead to a significantly higher concentration of drug in the upper and lower airways without causing systemic side effects, although therapeutic trials in children with tracheostomy tubes are lacking. Several preventative measures such as regular airway clearance and the use of a speaking valve may mitigate the risk of developing respiratory infections.